Understanding inappropriate hospital admissions of patients presenting to the Emergency Department (Italian Journal of Public Health, 2005)
Objectives. To identify 1) the characteristics of patients receiving non acute (inappropriate) care and 2) thevariables associated to inappropriate hospital use, in order to 3) estimate the relevance of the problem andto 4) focus future concurrent reviews and efforts to allocate patients to alternative health care settings.Design. A prospective review of a random sample of adult patients who presented to the EmergencyDepartment of the Molinette Hospital. Patients were assessed at admission and on day 3, 5 and 8 using theAppropriateness Evaluation Protocol (Italian validated version). Patients: 490 overall; 312 (64 %) medicaland 178 (36 %) surgical.Outcome measures. Acute (appropriate) and non acute (inappropriate) admissions, Major Disease Category,costs, mean weights of Diagnosis Related Groups, and length of stay (days).Results. The proportion of patients requiring acute care declined rapidly from presentation (84.5%) to thefifth day of admission (60.9%). Patients admitted during weekends showed a higher rate of inappropriatestay on day 5 (P=0.04). The proportion of inappropriate admissions was higher for medical rather thansurgical patients (P=0.07) at presentation and at day 5 (P < 0.01). Traditional social-demographic variableswere not significant risk indicators for inappropriate admissions. The likelihood ratio for inappropriateadmission at presentation was significantly higher for minor illnesses and disturbances (P=0.03).Inappropriate stay on day 5 was significantly associated with lower cost (P < 0.01), lower mean DRG weight(P < 0.01) and shorter length of stay (P=0.05) for medical but not for surgical admissions.Conclusions. Traditional epidemiological indicators are inadequate to target prospective concurrent reviews.Qualitative studies focusing on patient physician dialogue in different situations and contexts could widenour understanding of the problem and suggest new theoretical frameworks and theories to provide us withmore detailed explanations.
Keywords: appropriateness of care; concurrent review; indicators of inappropriate use; mergency Departments; costs